Integrating the Prophet's Diet in Contemporary Nutrition Education to Achieve Sustainable Health and Wellbeing: A Narrative Review - Anshory, Jamil; Wijaya, Heri; Noviasty, Reny; Joto, Nur Abri (Perhimpunan Intelektual Muslim Indonesia, 2024)
Nutrition education is essential for improving global health and achieving sustainability goals. According to the WHO 2023 report, 38% of adults worldwide are overweight, and 22% of children under five are stunted. The 2030 Sustainable Development Goals (SDGs), particularly SDG 2, emphasize the importance of nutrition education in promoting health and sustainable well-being. This study aims to explore the diet of the Prophet and its alignment with contemporary nutrition education principles to address current health challenges like obesity and malnutrition. A narrative review was conducted, analyzing 926 articles, 16 of which met the inclusion criteria. The articles, primarily published between 2016 and 2022, were sourced from databases such as Google Scholar, Scopus, and PubMed. The review focused on the principles of the Prophet’s diet and their relevance to modern nutrition education. The analysis revealed that the Prophet’s simple and balanced diet, including the principles of halal food, aligns with contemporary nutrition principles advocating natural and balanced eating. The findings highlight the growing interest in integrating Islamic dietary practices into nutrition education to promote sustainable health. This study suggests that incorporating the Prophet’s dietary principles into nutrition education can provide a sustainable, evidence-based approach to addressing modern health issues. The findings can inform the development of curricula and digital platforms. Future research should focus on empirical studies to assess the impact of these diets and create educational programs that integrate Islamic values.